From regulation to instruction: Embedding legal English in Indonesian law schools through ESP - Susanti, Ani; Putri , Uni Tsulasi (BAHASTRA, 2025)
This study investigates the integration of Legal English into Indonesian law schools, emphasizing the persistent gap between national language policy and pedagogical implementation. Although Indonesian regulations, such as Law No. 24 of 2009 and Law and Human Rights Ministerial Regulation No. 13 of 2018, recognize the use of English in legal communication, its curricular application remains fragmented and discretionary. Adopting an interdisciplinary mixed approach that combines doctrinal legal analysis, English for Specific Purposes (ESP) literature review, and questionnaire-based inquiry involving law students and lecturers, this study examines how policy mandates are interpreted in classroom practice. Findings reveal a clear policy–practice misalignment: Legal English is often treated as an elective subject, lecturers lack institutional support and ESP training, and students report limited opportunities for structured instruction despite acknowledging its importance for professional competence. The paper uniquely bridges regulatory and pedagogical perspectives by demonstrating how doctrinal frameworks can inform curriculum reform through Content-Based Instruction (CBI), Task-Based Learning (TBL), and mediation-oriented pedagogy. By aligning regulatory obligations with evidence-based ESP principles, the study proposes practical strategies for curriculum design, faculty development, and institutional policy to strengthen Legal English as a core component of legal education in Indonesia.